Natural resource management in an energy‐constrained future in the United States. (10th January 2014) - Svedarsky, W. Daniel; Trauger, David L.; Schad, David R.
ABSTRACT The plenary theme at the 2008 annual conference of The Wildlife Society was, "Thriving within limits: toward a scenario of hope." Wildlife professionals are still grappling with how wildlife management relates to sustainability as global limits, especially energy, become more obvious in affecting resource management. "Sustainability" as used in this paper is derived from the commonly cited, Brundtland Report definition of sustainable development as, "…development that meets the needs of the present without compromising the ability of future generations to meet their own needs." Further, it is activity that simultaneously addresses the interlinked aspects of economy, environment, and social well‐being. To be effective in the future, natural resources agencies and organizations (NGOs) will be compelled to 1) reduce energy use by increasing efficiency of unavoidable uses and reducing optional energy uses; 2) anticipate how energy costs will affect resource use by various stakeholders; and 3) mitigate climate change by reducing combustion processes and thereby greenhouse gases. Because of their fundamental missions, natural resource entities have a special obligation to employ exemplary conservation practices. Challenges are great, but opportunities are significant. Higher fuel costs will constrain some management practices, but may limit further development of more rural and underdeveloped lands, thereby reducing habitat fragmentation and often wildlife damage complaints. Will energy costs promote smaller vehicles, reduction of some management practices, greater focus on recreational areas closer to population centers, consolidation of offices with other entities, and more video‐conferencing of meetings? Will wildlife management be effectively integrated into landscapes where energy crops are produced along with food and where "life‐cycle analysis" measures the full ecological footprint of land management? Agencies and NGOs can partner with stakeholders to design landscape use that is more sustainable (less pollution, conserving of energy and soil, more biologically diverse), provides better connections to nature, and enhances overall resource conservation. Educational institutions have a critical role because they are instrumental in preparing future resource managers. © 2014 The Wildlife Society. © 2014 The Wildlife Society.